Variation of Mechanical Characteristics and Microstructural Evolution in AISI 316 Austenitic Stainless Steel Subjected to Long-Term Thermal Aging at Elevated Temperature - Kim, C.S. (Проблемы прочности, 2017)
The objective of this study was to investigate the mechanical degradation of AISI 316 austenite stainless steel as light-water reactor pressure vessel materials in the primary system of nuclear power plants. The influences of long-term aging on the microstructural and mechanical characteristics were studied. Исследована механическая деградация аустенитной нержавеющей стали AISI 316, которая применяется в качестве материала для сосудов давления легководного ядерного реактора в первичной системе атомных электростанций. Изучено влияние длительного старения на микроструктуру и механические характеристики. Досліджено механічну деградацію аустенітної нержавіючої сталі AISI 316, яка використовується як матеріал для посудин тиску легководного ядерного реактора в первинній системі атомних електростанцій. Вивчено вплив тривалого старіння на мікроструктуру і механічні характеристики.